Standardized precipitation evapotranspiration index (SPEI) as a tool to determine the hydrological dynamic of plains regions (Argentina) - Bohn, Vanesa Yael (2018)
The Standardized Precipitation Evaporation Index (SPEI) in a 12-months timescale was used to define wet, normal and dry cycles in four representative sites of climatic sub regions of the Central Plains of Argentina. The studied period was 1980-2016. Hydrological dynamic was defined by analysis of shallow lakes areal variations and hydrological deficits and exceeds calculation. Data ranges and frequency of data were statistically analyzed. Along the studied period, the frequency of normal and humid years was higher than the dry ones. Nineteen eighty-five, 2008 and 2009 were some dry years, defined by SPEI. Effectively, regarding hydrological dynamic, there was noted a decrease (from 0.9 % to 96 %) of the shallow lakes areas during the aforementioned periods, in relation with their area during the humid ones. Hydrological deficit were noted during the 1995 and 2008 dry years in the site of the north and the rest of the sites, respectively. Also, exceeds amounts showed a response to the climatological cycles, during extremely wet years (i.e.: 1998 (NW of the studied area), 2001 (center), 2002 (NE) and 2009, in the northern site).